SOME IMPORTANT ASPECTS OF ENGLISH ANECDOTES - Usmonova, Sevara Sultanovna; Karimova, Kamola Rustam qizi (Innovative Development in Educational Activities, 2022)
This article highlights some important aspects of anecdotes in spoken language. In addition, in what situations anecdotes are used, by whom they are told, and different tariffs are given in this article